2010
DOI: 10.1186/1471-227x-10-11
|View full text |Cite
|
Sign up to set email alerts
|

Improving rigid fiberoptic intubation: a comparison of the Bonfils Intubating Fiberscope™ with a novel modification

Abstract: BackgroundThe Bonfils intubating fiberscope has a limited upward tip angle of 40° and requires retromolar entry into the hypopharynx. These factors may make its use less desirable when managing the difficult airway because most anesthesia providers are well versed in midline oral intubation rather than the lateral retromolar approach. The Center for Advanced Technology and Telemedicine at the University of Nebraska Medical Center has developed a novel fiberscope with a more anterior 60° curve to allow for easi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…A potential explanation for the superior results seen with the VS over other rigid stylets could be the flexible tip, which allows for easier navigation of the airway. Preceding studies have shown improved success rates using rigid stylets with different curvatures [ 17 ]. An additional reason for faster and easier intubation with the VS compared to the VL is that the pathway to the cords to be navigated by the ETT have already been visualized by the VS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential explanation for the superior results seen with the VS over other rigid stylets could be the flexible tip, which allows for easier navigation of the airway. Preceding studies have shown improved success rates using rigid stylets with different curvatures [ 17 ]. An additional reason for faster and easier intubation with the VS compared to the VL is that the pathway to the cords to be navigated by the ETT have already been visualized by the VS.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent trials also showed a similar but shorter median total time to intubation between the two devices. On the sixth trial, the total time to intubation was similar between devices (VS 12 [9.25-15.75] sec vs VL 14 [13][14][15][16][17] sec, P = 0.21); however, the total time to intubation was significantly shorter compared to the first trial for each corresponding device (VS 21 sec vs 12.0s sec P = 0.0028 and VL 21.5 sec vs 14 sec P = 0.027).…”
Section: Plos Onementioning
confidence: 91%
“…The flexible fibreoptic intubation seems to cause a lesser haemodynamic response because we can better centralize its mobile distal tip thus minimizing the stimulation of the laryngeal surface. Bonfils rigid intubation endoscope has an immobile tip[ 1 20 ] thus having a higher probability of stimulating the laryngeal surface. The intubation time with bonfils rigid intubation endoscope might be longer, as we have to manipulate its immobile tip with our wrist, to visualize the vocal cords.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the average intubation time with the BIF was 50.0–52.8 s, which was close to the upper limit of the time range of 23–52 s reported previously [ 6 , 12 , 14 ]. Differences in approach such as left molar approach, para-tongue approach, or modified laryngoscopic structure [ 15 ] are possible factors affecting intubation time. Different methods can be used to judge successful intubation, such as the carbon dioxide test or lung auscultation, which may have different durations and lead to different time points, thereby exerting different effects on the results.…”
Section: Discussionmentioning
confidence: 99%